What’s in a Learning Theory? A Comparison of Contemporary Learning Theories, Their Shared Elements, and Their Vision of Society’s Role in Learning - Alexis Cherewka (Adult Education Research Conference, 2019)
Through discourse analysis of major theories of learning, this paper analyzes the role attributed to the social in contemporary learning theories in the field of adult education.
Keywords: adults; learning theories; society